Barriers to leisure-time physical activity in adults living in a low socioeconomic area of the Brazilian Southeast - Michele Santos Cruz; Leandro Martin Totaro Garcia; Douglas Roque Andrade; Alex Antonio Florindo (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to describe the main perceived barriers to engagement in leisure-time physical activity and associated factors among adults from the Ermelino Matarazzo district, Sao Paulo, Southeast, Brazil. Data were obtained from a population-based household survey conducted in 2007 involving 889 subjects (≥ 18 years). The long version of the International Physical Activity Questionnaire was used to identify physically inactive individuals. Open question about barriers was applied only for people inactive in leisure and content analysis was conducted to categorize the barriers. Descriptive analysis was performed using frequencies. Bivariate associations between the five most frequently reported barriers and sociodemographic variables, reported diagnoses of chronic diseases, nutritional status, working timing, travel time (to work and school), and television watching were determined using the chi-square test. Results showed that the five most prevalent barriers were lack of time (39.7%), lack of desire or motivation (18.4%), dislike exercising (6.3%), have an injury or disease (5.6%), and lack of money (3.6%). The vulnerable groups to lack of time were people married, young and middle aged, and with longer labor journey. Health problems were related by people with hypertension, diabetes, heart diseases, elderly, with low education and who did not have labor activities. People who were not working, with low education and income, and with hypertension related more dislike of exercising. Lack of desire or motivation was most cited among people who watched television. These results are important to support community programs promoting leisure-time physical activity in areas with low socioeconomic status.